Usage of growing pyramidal networks and system analysis methods in formalization of user model of Information Networks - Smirnova, Anastasiia (Technology audit and production reserves, 2015)
In this paper approach to development of user model of Information Networks is presented as fuzzy formalized object and using methods of system analysis. The aim of research is increasing of efficiency and reliability on Information Networks modeling by formalization of one of the most important input parameters: model of Information Networks user. Complexity of object which is Information Networks user is in its versatility, unevident relations and connections between its parameters and severeness of parameters location. Existing methods of system analysis for complex objects are developed for usage in concrete object areas and so this methodology for Information technologies area was not suggested yet. According to development of user model of Information Networks should be provided by heuristic methods using methods of system analysis of fuzzy formalized objects. In this paper method of growing pyramidal networks is proposed to be used as tool of development of Information Networks user mode. It allows recover connections within non-correlated parameters and proposes classes of users based on parameters and users needs. Information Networks users’ mode is supposed to be used in modeling and development of Information Networks, predictions of its growth based on its changing inner parameters and need of Information Networks users.